The dilemma of incumbents in sustainability transitions: A narrative approach - Karoline Augenstein; Alexandra Palzkill (Administrative Sciences, 2016)
In the context of the larger sustainability discourse, "sufficiency" is beginning to emerge as a new value throughout Western societies, and the question asked in this article is: Can we observe and conceptually identify opportunities to link successful business strategies of incumbents to principles of sufficiency? Thus, how feasible is sustainable entrepreneurship for incumbents? In this paper, a conceptual approach is developed combining insights from sociology, transition research, management and sustainable entrepreneurship research with a focus on narratives as a translation mechanism in situations where tensions emerge between corporate narratives and unexpected societal trends, e.g., the emergence of sufficient lifestyles. It will be shown that even though these are still a niche phenomenon, a focus on corporate narratives is an important element in understanding the role of incumbents in transitions to sustainability.
Keywords: 350; incumbents and sufficiency; corporate narratives; dilemma management; sustainability transitions